Post-war justice for the Nazi murders of patients in Kherson, Ukraine: comparing German and Soviet trials - Penter, Tanja (Guilt, 2022)
Under German occupation in World War II, tens of thousands of sick and disabled people were killed in the occupied Soviet Union. Very few German perpetrators were convicted for these crimes by courts in the Federal Republic after the war, whereas in the Soviet Union hundreds of thousands of Soviet citizens were sentenced to long prison terms or death as Nazi collaborators. Using the example of the murder of more than 1,000 mentally ill people at a psychiatric hospital in the Black Sea port city of Kherson, this article examines how investigative authorities and courts in Germany and the Soviet Union dealt with guilt, and asks whether criminal prosecutions have productive effects compared to impunity, particularly with respect to the culture of remembrance.